Samuel Butler, Victorian against the grain : a critical overview - Paradis, James G., 1942- (University of Toronto Press, 2007)
Samuel Butler, Victorian against the Grain is an interdisciplinary collection of essays that provides a critical overview of Butler's career, one which places his multifaceted body of work within the cultural framework of the Victorian age.